Penggunaan metode role playing pada mata pelajaran IPA materi hubungan makhluk hidup dengan lingkungannya di kelas 4 - Apriliani, Yasinta (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the use of the role playing method in Natural Sciences (IPA) subjects regarding the relationship between living things and their environment in Class IV. This research uses qualitative methods. Data collection techniques include observation and interviews. Observations are carried out while learning is taking place. And interview instruments were carried out with students to determine their interest in role playing. The results of this research show that using the role playing method in science subjects can help improve students' understanding of the material being studied.